2000
DOI: 10.1073/pnas.97.2.559
|View full text |Cite
|
Sign up to set email alerts
|

A highly efficient and robust cell-free protein synthesis system prepared from wheat embryos: Plants apparently contain a suicide system directed at ribosomes

Abstract: Current cell-free protein synthesis systems can synthesize proteins with high speed and accuracy, but produce only a low yield because of their instability over time. Here we describe the preparation of a highly efficient but also robust cell-free system from wheat embryos. We first investigated the source of the instability of existing systems in light of endogenous ribosome-inactivating proteins and found that ribosome inactivation by tritin occurs already during extract preparation and continues during incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
261
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 434 publications
(267 citation statements)
references
References 38 publications
4
261
0
Order By: Relevance
“…Yeast Trm8-Trm82 heterodimer was synthesized by a wheat germ in vitro translation system [25][26][27][28]. Because there was a 6 · His tag sequence expressed at the N-terminus of Trm82, the synthesized enzyme could be purified by Ni-NTA superflow column chromatography and DE52 column chromatography [28].…”
Section: Preparation Of Yeast Trna (M 7 G46) Methyltransferasementioning
confidence: 99%
See 1 more Smart Citation
“…Yeast Trm8-Trm82 heterodimer was synthesized by a wheat germ in vitro translation system [25][26][27][28]. Because there was a 6 · His tag sequence expressed at the N-terminus of Trm82, the synthesized enzyme could be purified by Ni-NTA superflow column chromatography and DE52 column chromatography [28].…”
Section: Preparation Of Yeast Trna (M 7 G46) Methyltransferasementioning
confidence: 99%
“…Cuvettes with a 1 mm path length were used. Each sample in the annealing buffer was pre-incubated at 15,20,25,30,35,40,45, 50, 55, 60, 65 or 70°C for 15 min and then the spectrum was recorded from 300 to 200 nm at each temperature. The scan was repeated three times.…”
Section: Measurement Of Enzyme Activitymentioning
confidence: 99%
“…OPN derived from the MRL and C3H alleles were prepared with a cell-free protein synthesis system using wheat germ ribosomal RNA, with which there is efficient protein synthesis without risk of LPS contamination [44]. In brief, Opn cDNA derived from an MRL/lpr or C3H/lpr mouse was inserted into pGEX-6P-1 J expression vector (Amersham Bioscience, Piscataway, NJ) containing a glutathione S-transferase (GST) tag region.…”
Section: Synthesis Of Polymorphic Opnmentioning
confidence: 99%
“…It was detached from column-conjugated GST using PreScission J protease (Amersham Bioscience). The purity of the OPN fraction was confirmed by SDS-PAGE, autoradiography of SDS-PAGE with 14 C-labeled synthetic OPN using a BAS-2000 Phosphoimager (Fuji, Tokyo, Japan) [44] and by Western blotting analysis using rabbit anti-murine OPN antibody (Cosmo Bio, Tokyo, Japan). OPN concentration was measured with an ELISA kit (Mouse osteopontin detection kit J , Immuno-Biological Laboratories, Fujioka, Japan).…”
Section: Synthesis Of Polymorphic Opnmentioning
confidence: 99%
“…These are usually based on either E. coli cell lysates (Kim et al, 1996), wheat germ cell lysates (Madin et al, 2000) or reticulocyte cell lysates (Craig et al, 1992), although other systems based on S. cerevisiae (Tuite et al, 1980) and Drosophila melanogaster (Scott et al, 1997) have also been reported. Some of these systems have been optimized for high-throughput genome-wide applications (Sawasaki et al, 2002;Busso et al, 2003).…”
Section: Recombinant Protein Expression From Cdna Librariesmentioning
confidence: 99%